Serotonergic impairment and memory deficits in adolescent rats after binge exposure of methylone. (November 2014) - López-Arnau, Raúl; Martínez-Clemente, José; Pubill, David; Escubedo, Elena; Camarasa, Jorge
Methylone is a cathinone derivative that has recently emerged as a designer drug of abuse in Europe and the USA. Studies on the acute and long-term neurotoxicity of cathinones are starting to be conducted. We investigated the neurochemical/enzymatic changes indicative of neurotoxicity after methylone administration (4 × 20 mg/kg, subcutaneously, per day with 3 h intervals) to adolescent rats, to model human recreational use. In addition, we studied the effect of methylone on spatial learning ad memory using the Morris water maze paradigm. Our experiments were carried out at a high ambient temperature to simulate the hot conditions found in dance clubs where the drug is consumed. We observed a hyperthermic response to methylone that reached a peak 30 min after each dose. We determined a serotonergic impairment in methylone-treated rats, especially in the frontal cortex, where it was accompanied by astrogliosis. Some serotonergic alterations were also present in the hippocampus and striatum. No significant neurotoxic effect on the dopaminergic system was identified. Methylone-treated animals only displayed impairments in the probe trial of the Morris water maze, which concerns reference memory, while the spatial learning process seemed to be preserved.